2012
DOI: 10.1155/2012/906252
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Polyphenols and Their Potential Benefits for Human Health

Abstract: This paper compiles the beneficial effects of cocoa polyphenols on human health, especially with regard to cardiovascular and inflammatory diseases, metabolic disorders, and cancer prevention. Their antioxidant properties may be responsible for many of their pharmacological effects, including the inhibition of lipid peroxidation and the protection of LDL-cholesterol against oxidation, and increase resistance to oxidative stress. The phenolics from cocoa also modify the glycemic response and the lipid profile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 98 publications
6
144
0
10
Order By: Relevance
“…Despite the drawbacks related to the high caloric intake associated with this practice, several potential benefits on different main systems in the human physiology have been investigated, namely in the cardiovascular, immunological, and neurological systems [1]. Many of the advantages of chocolate consumption have been attributed to the properties of some of its components, such as the polyphenolic structures named flavonoids (specially procyanidins and flavanols) [2] and also the methylxanthine compounds present in chocolate, namely caffeine and theobromine [3]. In the past few years, the existence of enhancing cognitive effects and improvement in mood related to chocolate or chocolate components has been emphasized [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the drawbacks related to the high caloric intake associated with this practice, several potential benefits on different main systems in the human physiology have been investigated, namely in the cardiovascular, immunological, and neurological systems [1]. Many of the advantages of chocolate consumption have been attributed to the properties of some of its components, such as the polyphenolic structures named flavonoids (specially procyanidins and flavanols) [2] and also the methylxanthine compounds present in chocolate, namely caffeine and theobromine [3]. In the past few years, the existence of enhancing cognitive effects and improvement in mood related to chocolate or chocolate components has been emphasized [4].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Martin et al (2008) reported cocoa polyphenols have a protective effect against oxidative stress in human hepatocellular carcinoma. [21] Cocoa therapy prior to induction of oxidative stress preventing DNA damage and increase the activity of antioxidant enzymes gluthatione reductase and gluthatione peroxidase on induced cell prooxidant tert-buthylhydroperoxide. [17] In this study also showed an increase in protective effect on levels of 8-OHdG in line with increasing concentrations of the cocoa extract.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies that cocoa has a proapoptotic effect via down regulation of Bcl-2. [12] Proapoptotic effect is determined by the positive ratio between BAX and Bcl-2, then induces the release of cytochrome C from mitochondria which is the determinant of apoptosis. [13] Applications DMBA shown to induce free radicals that damage DNA.…”
Section: Dmba-tpa Application Effect At Various Treatment Groups On Tmentioning
confidence: 99%
“…Statistical analysis showed cocoa 400 ppm group proved to have a preventive effect on the expression of Bcl-2 better than cocoa 800 ppm group Consistent with previous studies that cocoa has a proapoptotic effect via down regulation of Bcl-2. [12] Proapoptotic effect is determined by the positive ratio between BAX and Bcl-2, then induces the release of cytochrome C from mitochondria which is the determinant of apoptosis. [13] Anti-oxidant effects of cocoa extract in this study according to the results of Elisa examination that showed 400 ppm is the best treatment group as antioxidants and prevent increase expression of Bcl-2.…”
Section: Dmba-tpa Application Effect At Various Treatment Groups On Tmentioning
confidence: 99%